Colloidal Nanoparticles in Biotechnology - Elaissari, Abdelhamid;Ed (Wiley-Interscience, 2008)
The first book to discuss how nanoparticles can be used in biotechnological applications such as biomedical diagnostics and environmental analyses. Discusses novel applications of force measurements as a tool for medical diagnostics and fluorescent colloidal particles as detection tools in biotechnological systems.